Well, honey, to simplify x times 3, you just multiply them together. So, the answer is 3x. It's as simple as that, darling.
simplify the square foor of 49 times x to the third time y to the sixth times the absolute value of z squared
Log(3 * 1/3) = log(1) = 0
6y
Oh, dude, x times y equals the product of x and y. It's like when you have x groups of y things, and you're too lazy to count them all out individually, so you just multiply them together and call it a day. Math, man, it's wild.
Factor out the 4. The answer is y-3/y+3
It is y^3/x^2
Solution: 2y + 4 = 3 + y Combine like terms: 2y - y = 3 - 4 Simplify further: y = -1
The answer is 20.you get this answer by reading the instructions.
x4y3Answer BIt can be written as x4y3 but it can be switched around such as:4x3y. This means 4 lots of x's and 3 lots of y's or 4x times 3y.Ermm I could be wrong.
One step you usually want to take is to move any perfect square out of the radical. Example 1, with numbers: root(12) = root(4x3) = root(4) x root(3) = 2 root(3) Example 2, with variables: root(y cubed) = root(y squared times y) = root(y squared) times root(y) = y root(y)
Presuming you mean x/7 = y/3 times both by 21 (they are both factors of 21) That would give you 3x = 7y You cannot simplify the expression so that is your answer
(x2y2)3 + (x3y3)2 = 2x6y6.
4(y - 3) + 9 - 3y
If x = -7 and y = -3 then 5(-7) -2(-3) = -29
The answer is -60
Well, honey, to simplify x times 3, you just multiply them together. So, the answer is 3x. It's as simple as that, darling.